Valuing the economic benefits of species recovery programmes - E. Browning; M. Christie; M. Czajkowski; A. Chalak; R. Drummond; N. Hanley; K. E. Jones; J. Kuyer; A. Provins (People and Nature, 2024)
Abstract Accounting for the values placed on nature by the public is key to successful policies in reversing ongoing biodiversity declines. However, biodiversity values are rarely included in policy decisions, resulting in poorer outcomes for people and nature. Our paper addresses an important evidence gap related to the non‐availability of values for appraising large‐scale policies and investment programmes for species recovery and habitat improvement at the national level. We use a stated preference choice modelling approach to estimate household preferences and Willingness to Pay for species recovery and habitat improvement over a wide range of habitats in England. The framing of our stated preference study is crucial to the evidence we develop. Within the study, we define species recovery as incremental improvements to habitat quality and present respondents with choices between conservation policy options that improve different habitat types. We then use the response data to estimate values for habitat quality improvements, and the associated improvements to species presence and abundance. We are thus able to estimate economic benefits for ‘wild species recovery’ simultaneously across a wide range of habitat types. Willingness to pay values for habitat improvement was found to be highest for improvements from ‘moderate’ to ‘full’ species recovery by 2042; and for habitat types which have relatively low current extents in England, such as lowland fens. Policy Implications: biodiversity policy designers can make use of stated preference methods to guide decisions over which aspects of biodiversity targets to focus more resources on, since this enables policy to reflect public preferences, and thus engages higher public support for conservation. In our specific data and context, this implies prioritising the restoration of species recovery to high levels and focussing resources on scarcer rather than more abundant habitat types. Read the free Plain Language Summary for this article on the Journal blog.